All-sky Meteor Orbit System AMOS and preliminary analysis of three unusual meteor showers. (1st December 2015) - Tóth, Juraj; Kornoš, Leonard; Zigo, Pavol; Gajdoš, Štefan; Kalmančok, Dušan; Világi, Jozef; Šimon, Jaroslav; Vereš, Peter; Šilha, Jiří; Buček, Marek; Galád, Adrián; Rusňák, Patrik; et al.
Abstract: All-sky Meteor Orbit System (AMOS) is a semi-autonomous video observatory for detection of transient events on the sky, mostly the meteors. Its hardware and software development and permanent placement on several locations in Slovakia allowed the establishment of Slovak Video Meteor Network (SVMN) monitoring meteor activity above the Central Europe. The data reduction, orbital determination and additional results from AMOS cameras – the SVMN database – as well as from observational expeditions on Canary Islands and in Canada provided dynamical and physical data for better understanding of mutual connections between parent bodies of asteroids and comets and their meteoroid streams. We present preliminary results on exceptional and rare meteor streams such as September ϵ Perseids (SPE) originated from unknown long periodic comet on a retrograde orbit, suspected asteroidal meteor stream of April α Comae Berenicids (ACO) in the orbit of meteorites Příbram and Neuschwanstein and newly observed meteor stream Camelopardalids (CAM) originated from Jupiter family comet 209P/Linear. Abstract : Highlights: We demonstrated the capability of the AMOS cameras and SVMN network. We analyzed September ϵ Perseid (SPE) meteor shower outburst in 2013. We performed observation of April α Comae Berenicids (ACO) from Canary Islands. We confirm a weak activity of meteor shower Camelopardalids (CAM) in 2014.